Enhanced cytotoxicity of photoaged phenol-formaldehyde resins microplastics: Combined effects of environmentally persistent free radicals, reactive oxygen species, and conjugated carbonyls - Zhu, Kecheng; Jia, Hanzhong; Sun, Yajiao; Dai, Yunchao; Zhang, Chi; Guo, Xuetao; Wang, Tiecheng; Zhu, Lingyan (Environment international, 2020)
[Display omitted] •Photoaging under simulated sunlight irradiation enhanced the OP of PF-MP.•Simulated sunlight led to the increased generation of EPFRs and ROS in PF-MP.•The generated active species in PF-MP contributed to the elevated OP of PF-MP.•The PF-MP with an increased OP induced a higher cytotoxicity. Phenol-formaldehyde resin microplastic (PF-MP) is one of the major inhalable microplastics in environments released from the manufacture, processing and usage of PF materials. The associated toxicities of PF-MP might be affected by photoaging. In this study, the dynamic evolutions of the oxidative potential (OP) and redox-active species, including environmentally persistent free radicals (EPFRs), reactive oxygen species (ROS), peroxides and conjugated carbonyls, as well as the associated cytotoxicity of PF-MP were systematically investigated as a result of the simulated sunlight irradiation. As the photoaging time extended, the OP of PF-MP increased. The contents of the produced conjugated carbonyls, ROS and PF-bound EPFRs due to light irradiation increased as well, and displayed significant correlations with the OP (Spearman r > 0.6, p < 0.05). The photoaged PF-MP distinctly increased the cellular ROS and reduced the cell viability of human lung epithelial adenocarcinoma cells (A549). The cytotoxicity of PF-MP showed a similar trend with the OP level in PF-MP, suggesting that the produced active species induced the in vitro toxicities. The results not only highlight the adverse health effects of photoaged PF-MP, but also provide new perspectives for the environmental risks of airborne MPs.